(3OjhGf YHO GdMj GdNGd GdWGdhjs - (3YHO GdMj Hf Ydj Hf eMeO, J(B1117(3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejfhHYO ajbhdYHO GdMj Hf Ydj Hf eMeO Hf eMehO GdTgjQ HGHf GdWhjd GdMfajGdeYQha HGdNGdgPG eG fWb Hg dSGf GdMGd abGd Cf Jchf NeQI GdSeGY ZPG GdQhM hddge hGdcQhH LdGAs
(3BNQgG (B:s
(3Ch SbG TYWjg aj eG dj (B*** (3Ch ef GdedHhS hfOg , hCUjQ eLdS LfI (B*** (3ef Tje GdYhOG hfOgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 290s
(3eYLe GdeDdajf(B: 2 / 68s
(3EjVGM Gdecfhf(B: 1 / 500s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs